Análise comparativa do grau de abertura econômica, esforço exportador e dependência das importações do Brasil, Regiões e estados brasileiros – 2002 A 2019 - MENEZES, Alice Helena da Silva Pinto (2023)
The present study aims to analyze the evolution of the Degree of Economic Openness (GA) in Brazil, by regions and states, from 2002 to 2019. For the calculation, the conversion of monthly exports and imports from dollars to reais was made, by means of the nominal exchange rate, subsequently finding the annual value of exports and imports and their annual sum divided by the Gross Domestic Product. The main sources of the variables used come from the Special Secretariat for Foreign Trade and International Affairs - SECINT and the Brazilian Institute of Geography and Statistics (IBGE). The main results reveal that the North and South regions are the most commercially open, with a degree of openness higher than that of Brazil in all years, presenting a balanced foreign trade profile, with an Export bias, in most of the analyzed series. The Southeast Region followed the national pattern, also showing a balanced trade pattern with a slight export bias. The Midwest has evolved the most in terms of degree of openness in recent years, largely due to the results of the states of Mato Grosso and Mato Grosso do Sul. Finally, the Northeast had the lowest degree of economic openness, with two states belonging to the range of degree of openness below 5% of the gross domestic product.